Identifikasi Mikroplastik Pada Kerang Darah (Anadara granosa) DI Perairan Hutan Mangrove Labuhan Deli Kecamatan Medan Marelan Sumatera Utara - Putri Hawani Silalahi; Muftie Sudibyo (CV.ITTC INDONESIA, 2024)
Export-qualified Anadara granosa require microplastic-free criteria. The aim of this study was to determine the type, abundance, and colour of microplastics present in blood cockle meat. Sampling was conducted at three mussel farming stations in Young Pana Hijau, Marelan, Medan, with 30 samples each. Microplastic extraction was carried out by taking the clam's digestive tract, weighing it into a microtube and adding 10% KOH solution as much as 3:1 with the weight of the tissue, closed and allowed to stand for 24 hours at 40°C, 24 hours after in the centrifuge for 2 minutes at 500 rpm to precipitate all particles dissolved in the liquid. The solution on top was discarded and the solids on the bottom were taken for examination under a microscope. The results showed that microplastics were found in the digestive tract of mussels of fragment (75%), fibre (15%) and film (10%) types. The most dominant colours of microplastics were black (73%), red (12%), yellow (6%), brown (5%) and blue (4%). The presence of microplastics in cultured mussels indicates that the cultivation site needs to be reviewed to obtain a more hygienic quality of mussel meat.